2018
DOI: 10.3390/d10020017
|View full text |Cite
|
Sign up to set email alerts
|

Genotyping by Sequencing Reasserts the Close Relationship between Tef and Its Putative Wild Eragrostis Progenitors

Abstract: The genus Eragrostis consists of 350 species, including tef (Eragrostis tef (Zucc.) Trotter), the only cultivated species in this genus. Very little is known about the genetic potential of these species for tef improvement and genomics research. Here, we investigated a germplasm panel consisting of 40 Eragrostis species and 42 tef lines with single nucleotide polymorphism (SNP) data generated using the genotyping by sequencing (GBS) protocol. Thousands of SNPs were identified genome-wide from the germplasm pan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 72 publications
2
26
0
Order By: Relevance
“…However, the limited studies made to date revealed the existence of substantial differences among tef genotypes for diverse traits investigated (Assefa et al 2001(Assefa et al , 2015Chanyalew et al 2013). The most recent studies in diversity involved 188 tef genotypes (including 144 landraces) using morphological traits (Jifar et al 2018), 273 accessions using phenotypic traits (Ben-Zeev et al 2018) and 82 accessions including wild Eragrostis species using molecular markers (Girma et al 2018).…”
Section: Geneticsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the limited studies made to date revealed the existence of substantial differences among tef genotypes for diverse traits investigated (Assefa et al 2001(Assefa et al , 2015Chanyalew et al 2013). The most recent studies in diversity involved 188 tef genotypes (including 144 landraces) using morphological traits (Jifar et al 2018), 273 accessions using phenotypic traits (Ben-Zeev et al 2018) and 82 accessions including wild Eragrostis species using molecular markers (Girma et al 2018).…”
Section: Geneticsmentioning
confidence: 99%
“…The recent genotyping by sequencing (GBS) study involving 40 Eragrostis species and 42 tef lines showed that the wild Eragrostis species were more diverse than the tef cultivars indicating the usefulness of wild species in enriching the tef gene pools (Girma et al 2018).…”
Section: Molecular Markersmentioning
confidence: 99%
“…The germplasms collected were characterized at both phenotypic and genotypic levels. At the phenotypic level, various agro morphological descriptors were used for evaluation of orphan small cereal accessions (Ben‐Zeev et al., 2018; Nyam et al., 2017; Patil et al., 2019) whereas at the genotypic level a variety of molecular markers were used for genetic diversity and population structure studies (Girma et al., 2018; Lule et al., 2018; Manimekalai et al., 2018; Olodo et al., 2018; Yadav et al., 2016). This shows the significant importance of these markers that provide useful tools for population and evolutionary genetics studies of orphan small millets.…”
Section: Bottlenecks and Genomic Breeding Achievements In Orphan Small Grain Milletsmentioning
confidence: 99%
“…The consortium is committed to sequence the genome of 101 traditional African food crops with high nutritional value which include cereals, vegetables, root and tubers and fruit trees (AOCC 2018). Kumar et al (2016); Girma et al (2018); Rabbi et al (2014Rabbi et al ( , 2015…”
Section: African Orphan Crops Consortium (Aocc)mentioning
confidence: 99%
“…The project aims at improving the orphan cereal crop tef and it is hosted at the Institute of Plant Sciences at the University of Bern in Switzerland. The project employs key genetic and genomic tools (Esfeld et al 2013b;Girma et al 2018) and collaborates with the National Tef Improvement Program in Ethiopia to develop tef varieties with desirable traits (Cannarozzi et al 2018a;Kebede et al 2018). The group led an international group of scientists which resulted in the genome sequence of the draft genome of tef (Cannarozzi et al 2014).…”
Section: Tef Improvement Projectmentioning
confidence: 99%